Reflections on the Use of Visual Methods in a Qualitative Study of Domestic Kitchen Practices. (June 2016) - Wills, Wendy J; Dickinson, Angela M; Meah, Angela; Short, Frances
Understanding everyday social practices is challenging as many are mundane and taken for granted and therefore difficult to articulate or recall. This paper reflects on the challenges encountered in a qualitative study underpinned by current theories of practice that incorporated visual methods. Using this approach meant everyone in a sample of 20 household cases, from children through to adults in their 80s, could show and tell their own stories about domestic kitchen practices. Households co-produced visual data with the research team through kitchen tours, photography, diaries/scrapbooks, informal interviews and recording video footage. The visual data complemented and elaborated on the non-visual data and contradictions could be thoroughly interrogated. A significant challenge was handling the substantial insight revealed about a household through visual methods, in terms of household anonymity. The paper reflects on the challenges of a visual approach and the contribution it can make in an applied sociological study.